Scaling-Up Sustainable Cropping Practices: 'Zia' and 'Micro-dosing' - International Institute of Tropical Agriculture; Savannah Agricultural Research Institute (International Food Policy Research Institute, 2015)
This data study explores raising and sustaining productivity in cereal-legume cropping systems in northern Ghana. About the project. Project title: AfricaRISING - Sustainable Intensification of Cereal-Based Farming Systems in the Guinea-Sudan-Savanna of Ghana and Mali. Project abstract: In Ghana, Zia has been successfully been introduced on a limited scale to farmers in the East Gonja, East Mamprusi districts in the Northern region and Guru and Builsa district in Upper East region Presbyterian Agricultural Services. However, Zia farming is an innovative technology which involves the burial of manure/organic matter in holes/ pits and planting the crop later on top of the pit. The objectives of this study are to evaluate and disseminate the Zia and fertilizer Micro-dosing techniques on-farm; to undertake cost benefit analysis of the Zia and fertilizer Micro-dosing; to explore the potential increase in grain yield of Zia and fertilizer Micro-dosing over farmers practice in the Africa RISING intervention communities; to undertake comparative analysis of the effect of Zia and fertilizer Micro-dosing on maize,sorghum, and millet. Project website: http://africa-rising.net http://africa-rising.net/where-we-work/west-africa/